(untitled) (TAMADDUN NURI JURNALI, 2024)
This article thoroughly analyzes the meanings and uses of onomastic lexemes in the epic “Alpomish”, a sample of folk art. Onomastic lexemes in this saga can be expressed not only in anthroponyms, but also in zoonyms and phytonyms. The article analyzes the use of the text in different forms. In addition, the article examines verses where these lexemes are used, as well as their linguistic, cultural and social meanings. Statistical analyzes were carried out in the research work, which clearly show the practical importance of the work.